Effectiveness of Out-patient Therapeutic Program on Nutrition among Under Fives: A Retrospective Study of Kisumu East District, Kenya - Ahoya , Brenda; Andang‘o, Pauline; Ouma , Collins (African Journal of Education,Science and Technology (AJEST), 2013)
Outpatient Therapeutic Program (OTP) has been implemented with great success. Monitor ing and evaluation against program objectives is integral. This study aimed to assess effectiveness of OTP program in Kisumu East District and identify factors influencing its effectiveness.In a retrospective longitudinal study targeting malnourished child ren 6–59 months registered in OTP, information on type of malnutrition, HIV status, cure rate, defaulter rate, death rate, non -response, average weight gain and Average Length of Stay (ALOS) in the program were abstracted from hospital records of 420 eligi ble children between January to December 2009; selected by systematic random sampling. Proportions of Marasmus, Kwashiorkor, and HIV were determined. Proportions of outcomes were compared against Sphere standards to assess effectiveness. Associations between type of malnutrition and: HIV status, gender, age and Mid Upper Arm Circumference (MUAC) were determined using regression analysis. From the study findings, prevalence of Marasmus (67.4%) was higher than prevalence of Kwashiorkor (31.2%). Children cured were 54%, 3.3% died, 22.6% defaulted while non -responders were 0.7%. ALOS was 39 days and rate of weight gain 4.8g/kg/day. Regression analysis showed: MUAC and HIV status influenced type of malnutrition, low MUAC increased the chances of dying by 50% (CI 0.302 - 0.944 p=0.031) and each cm increase in MUAC reduced rate of weight gain by 0.8g/kg (CI -1.483 - -0.117 p=0.022). Increase in rate of weight gain increased cure rate by 8% (CI 1.024 - 1.15 p=0.006). The program was effective in achieving low death rates, ALOS and rate of weight gain. High defaulter rate may have obscured true death and cure rates. Factors contributing to high defaulter rates should be investigated and addressed to improve program effectiveness